A new β-cyclodextrin-encapsulated potassium ferrate composite (KFO@β-CD) for efficient removal of PPCPs from reclaimed water: Performance and degradation pathway. (October 2022) - Zhang, Jun; Quan, Xi; Li, Fu; Zhen, Chenxi; Yin, Linlin; Zuo, Wei; Tian, Yu
Abstract: Ferrate is increasingly used as an oxidant for chemical oxidation of pharmaceuticals and personal care products (PPCPs) in reclaimed water. However, the instability of ferrate in aqueous solution and its low content of active ingredients have limited its application in water purification. In this paper, a novel β-cyclodextrin encapsulated potassium ferrate composite (KFO@β-CD) is synthesized for the first time using a thermomelting-condensation method and used to degrade carbamazepine (CBZ). This study evaluates and demonstrates the superior stability, sustained release behavior and hygroscopic characteristics of KFO@β-CD. In-depth investigations show that KFO@β-CD with a mass ratio of 10:1 can degrade 85.2 % of CBZ in 60 min. Analyzing the transformation pathways of CBZ has shown that Fe(VI) performed more reactive with olefinic double bond owing to electron-rich organic moieties, which convert carbamazepine to oxidized products with low molecular weight. These results significantly improve the state of our knowledge about this highly efficient and stable oxidant, which is likely to be useful for further degradation of PPCPs. Graphical abstract: Unlabelled Image Highlights: Encapsulation of potassium ferrate by β-cyclodextrin using a thermomelting-condensation method. The enhanced stability of β-CD-encapsulated potassium ferrate (KFO@β-CD) compared with pure potassium ferrate. The reduced Fe(VI) release and hydroscopic rate with increased β-CD/KFO mass ratios. 85.24 % of CBZ degradation efficiency within 60 min. Selective attack of Fe(VI) to olefins of carbamazepine due to electron-rich organic moieties.